Development and Evaluation of a Primary HealthCare-based Physiotherapy Intervention and its Effects on Selected Indices of Stroke Recovery (2013)
Aim: To develop a Primary Healthcare-Based Physiotherapy Intervention (PHCPI) that requires simple, inexpensive, easy-to-use equipment for stroke rehabilitation and evaluate its effects on selected clinical indices of recovery among post-acute stroke survivors over a 10-week period. Methods: Three databases (Medline, Pubmed and PEDro) were used to identify treatment approaches with proven efficacy. The authors synthesised these treatment approaches to develop the PHCPI, which was used in a repeated measure design involving 25 (mean age=60.6 ± 10.2 years) consenting individuals with first-incidence stroke. These individuals were treated at a primary health centre, twice weekly for 10 consecutive weeks. Outcomes were assessed using the Modified Motor Assessment Scale (MMAS), the Short Form Postural Assessment Scale for Stroke (SF-PASS) and the Reintegration to Normal Living Index (RNLI), before the intervention and fortnightly thereafter. Walking speed and quality of life were also assessed before the intervention and at week 10 of it. Results: Within-subject multivariate analysis, after controlling for gender, showed a significant increase in motor function, postural balance, walking speed and quality of life. Their community reintegration scores also improved over the period. Conclusion: The PHCPI resulted in improved motor function, community reintegration, walking speed, postural balance and quality of life among community-dwelling stroke survivors. This intervention can be used for stroke rehabilitation at primary health centres.